PENGARUH STORE LAYOUT TERHADAP IMPULSE BUYING DI TOKO BUKU GRAMEDIA ISTANA PLAZA BANDUNG - Heni Rohaeni; Asti Damayanti (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2018)
Store layout is one of the retail marketing strategy elements named retail mix which can impact the purchasing. The objective of this research is to analyze how the effect of  store  layout in retail  marketing strategy  toward  impulse buying on Gramedia Books Store products at Istana Plaza Bandung. This research  applied quantitative approach  with non-probability  sampling method and  convenience technique. The sample of this research  is 100 visitors of Gramedia  Books Store at  Istana  Plaza Bandung. This research used questionnaire as research instrument with 21 questions and  analyze  with coefficient correlation  test,  coefficient determination  test,  and regression test. The result of this research indicate that the store layout have an effect toward impulse buying equal to 58,06% and the residue equal to 41,94% effected by some other  factor. The equal  of 58,06% show that  the store layout has a  strong relation toward impulse buying on Gramedia Book Store products at Istana Plaza Bandung. Keywords: Store Layout, Impulse Buying.